Hydration kinetics and compressive strength of low carbon binders - Umer, Muhammad (2024)
Lower clinker factors have been proposed as the most practical and economical way to decarbonize the concrete industry and are achieved by high level substitution of cement clinker with Supplementary cementitious materials (SCMs). However, reduction of global average clinker factor is curtailed by limited supply of traditional SCMs such as fly and slag. Due to this, alternate SCM sources are being investigated. Among these, natural pozzolans such as Volcanic Pozzolans from Iceland (VPI) have gained a resurgence in the Nordic region of Europe. Similarly, ternary blended cements in which limestone is added in addition to the SCM to further lower the clinker factor have been proposed. With replacement of cement with SCMs and limestone, the early age hydration kinetics are governed by an ensemble of several mechanisms such as alite and aluminate hydration, dilution and filler effects of limestone, and chemical effects of SCMs. All the more, participation of limestone in a chemical reaction with SCM has been reported. Therefore, developing our understanding of the effect of various SCMs on the hydration kinetics is essential to effectively lower the clinker factors. In this thesis, hydration kinetics of binary binders containing CEM I and SCMs (slag, VPI and fly ash at 40% replacement) and ternary binders containing 10% limestone in addition to 40% SCMs were investigated using isothermal calorimetry. Additionally, the compressive strength development up to 28 days was determined using mortar prisms tests and a correlation between the heat of hydration and compressive strength was established. The results showed that among the SCMs, VPI exhibited higher reactivity and compressive strength up to 2 days as compared to fly ash and slag, and was attributed to its finer particle size. Addition of limestone resulted in a decrease in the compressive strength of binders with slag and VPI where-as for fly ash-based binder, the strength remained intact with limestone addition. One possible explanation for this might be higher ...